THE IMPACT OF WATER ECOLOGY ON AGRICULTURAL PRODUCTS - Мусаева Muqaddas (American Journals Publishing, 2024)
This article is devoted to the issues of the impact of water ecology on agricultural products and increasing productivity, as well as increasing the productivity of irrigation waters. It is necessary to solve the problems of water ecology, which depend on the effectiveness of the cultivation of agricultural products, the composition and quality of the water used in the irrigation of crops. The transition to effective water saving methods promotes water ecology, which ensures water, food and environmental safety in the region, determines crop yields and helps to increase product efficiency. In agriculture, the yield of cotton was analyzed. Analyzes are determined not only by the yield, but also by the possibilities of increasing plant production.
Keywords: Water ecology, agriculture, method, analysis, productivity, water use, water resources.